Extension of the Periods for Consent to and Payment of Quota Increases. (Policy Papers; Policy Paper ;, 2019)
This paper proposes a further six-month extension of the period for members to consent to an increase in their quotas under the Fourteenth General Review of Quotas ("Fourteenth Review") through June 28, 2019.